Dermatologic approach to an umbilical mass - Joan Fernandez; Jacqueline A Guidry; Ida Orengo (Wolters Kluwer Medknow Publications, 2019)
The potential for bowel perforation in dermatology is rare; however, perforation remains an important consideration for lesions in and around the umbilicus. We present a case of a 74-year-old female who presented to the outpatient dermatology office for evaluation and biopsy of an umbilical mass. Due to the location, biopsy was deferred and the patient was sent for surgical consultation. The patient was later diagnosed with an incarcerated ventral hernia. We will discuss the differential diagnosis of umbilical masses and the possible complications associated with performing biopsies on lesions in this area.